2011
DOI: 10.1111/j.1468-2427.2011.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Population Growth in Peri‐Urban Accra, Ghana

Abstract: Urbanization in Africa (and the wider developing world for that matter) has often been misunderstood by Western observers on the lookout for Western‐style cities and suburbs. In these parts of the world, rapid urbanization has led to continuing changes in the form and shape of cities, as peri‐urban zones shift swiftly from rural to urban. While some descriptions of the peri‐urban zone suggest an amorphous area filled with low‐income residents, others argue that the zone is highly diverse. Using population cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 23 publications
5
60
0
1
Order By: Relevance
“…This explains why, according to our estimates, 90.5% of the population of GKMA lived within 4 kilometres of a highway as of 2010. This phenomenon has also been observed in other African metropolitan areas (see Briggs & Mwamfupe, 2000;Doan & Oduro, 2012;Grant & Yankson, 2003;Mabogunje, 1990). For example, Doan & Oduro (2012) found that, as of 2000, about 90% of the population of peri-urban Accra lived within 4 kilometres of a highway, which is very similar to what we found in GKMA.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This explains why, according to our estimates, 90.5% of the population of GKMA lived within 4 kilometres of a highway as of 2010. This phenomenon has also been observed in other African metropolitan areas (see Briggs & Mwamfupe, 2000;Doan & Oduro, 2012;Grant & Yankson, 2003;Mabogunje, 1990). For example, Doan & Oduro (2012) found that, as of 2000, about 90% of the population of peri-urban Accra lived within 4 kilometres of a highway, which is very similar to what we found in GKMA.…”
Section: Discussionsupporting
confidence: 80%
“…This model addresses the effects of road networks on urban spatial structure (see Chin, 2002;Doan & Oduro, 2012;Harvey & Clark, 1965). Progress in transportation technology and use of private automobiles has made it possible for urban residents to commute over long distances to the CBD and the suburbs.…”
Section: Ribbon Developmentmentioning
confidence: 99%
“…Accra had a human population of 377,558 in 1960 which increased to 1,657,856 in 2000 [10,11]. In 2010, Accra had an urban population of about 2.9 million and a metropolitan population of about 4 million [12].…”
Section: Study Areamentioning
confidence: 99%
“…It involves various transformations on the edges of large cities, such as transformation of existing rural settlements into urban settlements without necessarily displacing the rural residents (UNFPA, 2007) and changes in the structure of the peri-urban local economy, including changes in both sectorial composition of economic activities and labour force (Webster & Muller, 2002). It also involves changes in demography, social structure, land use, land use management and architecture in the peri-urban zone (Simon et al, 2004), as well as increased demand for land in peri-urban communities where indigenous and long-term settlers have depended on agriculture for centuries (see Oduro & Doan, 2012). example, a household may choose to produce its own food because it has access to land or some household members may participate in waged employment because they possess some employable skills (Rakodi, 2002;Scoones, 1998).…”
Section: Introductionmentioning
confidence: 99%